Smart dustbin - Krishnamurty, Devyashree; Mohan, Yoganand; Sidek, Noor Azizah (Multidisciplinary Applied Research and Innovation, 2022)
Recently, increase in population and urbanization has led to the increase in waste production. There are several problems with the current existing system that are being identified. This will reflect the need for a new efficient system for monitoring and manage the garbage. The main issues causing the prototype of the smart dustbin was people with disabilities or senior citizen sometimes not able to lift those dustbin cap to litter and poor waste disposal way. This project aims to integrate and test run the hardware (design of the dustbin) and software (Arduino Uno) to operate in the ideal working environment. The scope of the project should be viewed as a guide to ensuring that the project does not deviate from the goals to be reached at any point it is implemented. The waste should be in less than 5 metre range from dustbin and is limited for households or office use. This project presents the implementation of prototype of ultrasonic sensor for the use of the electric dustbin looking at the seriousness of the waste management issue. The prototype designs weighs the pros and cons of owning a smart dustbin and as well designing and implementing the simulation of prototype through SolidWorks 2019 software.